(untitled) (JURNAL KEPERAWATAN, 2014)
Abstrack: Introduction One factor that was instrumental in the nutritional status of children is parenting. Parenting is the interaction between children and parents during the conduct of activities parenting. parenting is to educate, guide and nurture children, care of food, drink, clothing, hygiene, or in everything case that is supposed to be needed, to the extent where the child has been able to carry out his needs are vital, such as eating, drinking, bathing and dressing. One of the mother’s affecting is, nutrition is influenced by the mother’s ability to provide sufficient food for children as well as parenting is influenced by factors family income, education, behavior and number of siblings. The purpose of this study is to find out about Mother Parenting Relationship with Nutritional Status in Puskesmas Ranotana Weru Wanea District of Manado. This research included in quantitative research using survey research methods and analytic studies using cross-sectional design. The samples in this study using a total sampling technique. In this research, statistical analysis using Chi Square with a limit of significance Î± = 0.05. Results of statistical tests initially using Chi-Square test obtained p = 0.001 <Î± = 0.05, which means that Ho is rejected. The conclusion of this study is there was a relationship between Mother Parenting Relationship with Nutritional Status in Puskesmas Ranotana Weru Wanea District of Manado Keywords: Mother Parenting, toddlers, Nutritional Status, Bibligraphy: 18 Book (2000-2014), 14 Journals Abstrak: Pendahuluan Salah satu faktor yang berperan penting dalam status gizi balita adalah pola asuh.Pola asuh merupakan interaksi antara anak dan orang tua selama mengadakan kegiatan pengasuhan. mengasuh anak adalah mendidik, membimbing dan memelihara anak, mengurus makanan, minuman, pakaian, kebersihannya, atau pada segala perkara yang seharusnya diperlukannya, sampai batas bilamana si anak telah mampu melaksanakan keperluannya yang vital, seperti makan, minum, mandi dan berpakaian. Salah satu yang mempengaruhinya yaitu ibu, keadaan gizi di pengaruhi oleh kemampuan ibu menyediakan pangan yang cukup untuk anak serta pola asuh yang di pengaruhi oleh faktor pendapatan keluarga, pendidikan, prilaku dan jumlah saudara. Tujuan penelitian ini ialah untuk mengetahui tentang pola asuh ibu dengan status gizi balita di wilayah kerja Puskesmas Ranotana Weru Kecamatan Wanea Kota Manado. Penelitian ini termasuk dalam jenis penelitian kuantitatif. metode penelitian menggunakan survei analitik dan desain penelitian menggunakan cross sectional. Pengambilan sampel dalam penelitian ini menggunakan tehnik total sampling. Hasil penelitian menggunakan analisis uji statistik Chi Square dengan batas kemaknaan Î± = 0,05. Hasil uji statistik didapatkan nilai p = 0,001<Î± = 0,05, yang berarti Ho ditolak. Kesimpulan penelitian ini yaitu ada hubungan antara pola asuh ibu dengan status gizi balita di wilayah kerja Puskesmas Ranotana Weru Kecamatan Wanea Kota Manado. Kata Kunci: Pola Asuh Ibu, Balita, Status Gizi Daftar pustaka : 18 buku (2000-2014), Jurnal 14